2018
DOI: 10.1002/1878-0261.12167
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of Wnt and Yes‐associated protein signaling retards the growth of triple‐negative breast cancer in both mesenchymal and epithelial states

Abstract: Triple‐negative breast cancer (TNBC), the most refractory subtype of breast cancer to current treatments, accounts disproportionately for the majority of breast cancer‐related deaths. This is largely due to cancer plasticity and the development of cancer stem cells (CSCs). Recently, distinct yet interconvertible mesenchymal‐like and epithelial‐like states have been revealed in breast CSCs. Thus, strategies capable of simultaneously inhibiting bulk and CSC populations in both mesenchymal and epithelial states h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 53 publications
6
56
0
Order By: Relevance
“…In addition to this information, YAP is a main player in Hippo and both WNT and Hippo pathways participate in various cellular developments of many diseases [34]. It was recently demonstrated that the YAP mediated by E-cadherin could be included in the destruction complex of β-catenin in order to orchestrate WNT signaling [35]. In this study, experimental results were consistent with the aforementioned studies that the mRNA and protein levels of β-catenin were increased in AIP lung fibroblasts.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to this information, YAP is a main player in Hippo and both WNT and Hippo pathways participate in various cellular developments of many diseases [34]. It was recently demonstrated that the YAP mediated by E-cadherin could be included in the destruction complex of β-catenin in order to orchestrate WNT signaling [35]. In this study, experimental results were consistent with the aforementioned studies that the mRNA and protein levels of β-catenin were increased in AIP lung fibroblasts.…”
Section: Discussionsupporting
confidence: 89%
“…This prediction is supported by our analysis of gene expression profiles of CSCs belonging to different cancer subtypes, and report the presence of epithelial, hybrid E/M and mesenchymal CSCs. Recent experimental studies have identified such heterogeneity in EMT status of different CSCs across cancer subtypes [10,12,36,[54][55][56][57], supporting the idea about a dynamic 'stemness window' [13] along the 'EMT axis'. Moreover, a recent clinical study identified different subsets of CTCs -those that expressed EMT markers but not stemness ones, those that expressed stemness markers but not EMT, those that expressed both EMT and stemness markers, and those that expressed neither.…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, Deb et al ( 163 ) identified two mutually exclusive clonal subpopulations in altered signaling states—one with upregulated pSTAT3 and the other with downregulated SMAD2/3—and targeted STAT3 and BCL6 (a transcription factor downstream of SMAD2/3) in a combinatorial manner to overcome non-genetic heterogeneity. Furthermore, dual inhibition of Wnt and Yes-associated protein (YAP) signaling can restrict the population of both epithelial-like and mesenchymal-like CSCs ( 164 ). These combinatorial therapies are reminiscent of combinations of drug pyrazinamide (that specifically targets M. tuberculosis persisters) with other canonical treatments ( 165 ).…”
Section: Implications Of Dynamic Phenotypic Plasticity and Stochasticmentioning
confidence: 99%